2020
DOI: 10.1055/s-0040-1721904
|View full text |Cite
|
Sign up to set email alerts
|

Association of Personal Protective Equipment with De Novo Headaches in Frontline Healthcare Workers during COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Objectives This study aimed to determine the association of personal protective equipment (PPE) usage with new-onset headaches and exacerbation of pre-existing headache disorders among healthcare workers at the frontlines during coronavirus disease 2019 (COVID-19) pandemic. Materials and Methods A descriptive cross-sectional survey was conducted across Pakistan in June–July 2020. The study was approved by Ethical Committee, Armed Forces Institute of Dentistry, Rawalpindi (IRB form no.905/Trg-ABP 1K2). A qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 36 publications
4
41
0
Order By: Relevance
“…The incidence of PPE-associated headaches amongst healthcare workers in the context of the COVID-19 pandemic ranges from 26.5%–90.7% [ 24 , 25 ••, 26 – 32 , 33 •, 34 •, 35 •, 36 •]. In comparison, a study amongst healthcare providers using the N95 face mask during the 2003 severe acute respiratory distress syndrome (SARS) epidemic in Singapore observed that new-onset face mask–associated headaches occurred with an incidence of 37.3% [ 37 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of PPE-associated headaches amongst healthcare workers in the context of the COVID-19 pandemic ranges from 26.5%–90.7% [ 24 , 25 ••, 26 – 32 , 33 •, 34 •, 35 •, 36 •]. In comparison, a study amongst healthcare providers using the N95 face mask during the 2003 severe acute respiratory distress syndrome (SARS) epidemic in Singapore observed that new-onset face mask–associated headaches occurred with an incidence of 37.3% [ 37 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Since the start of COVID-19 in December 2019, there have been a total of 6 published studies specifically conducted to understand PPE-associated headache amongst healthcare workers (see Table 1 ) [ 25 ••, 33 •, 34 •, 35 •, 36 •, 38 •]. Based on these studies, several factors have been found to confer a greater likelihood of developing de novo PPE-associated headaches.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Social distancing measures along with personal protective equipment should be emphasized once countries start or decide to lift restrictions for the sake of their respective economy even though they are struggling to flatten the pandemic curve. 15 This is because such measures can at least delay the rapid spread and allow the healthcare system to save time and resources intended for expanding capacity in testing and medical treatment. In this challenging period, South Korea provides evidence that the pandemic can be contained with less aggressive restrictions.…”
Section: Discussionmentioning
confidence: 99%